2020
DOI: 10.1186/s12885-020-6662-5
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG5 promotes nasopharyngeal carcinoma progression by regulating miR-1179/HMGB3 axis

Abstract: Background: Long noncoding RNAs (lncRNAs) have been reported to be important regulators in pathogenesis of human cancers, including nasopharyngeal carcinoma (NPC). Here, we mainly aimed to explore the mechanisms of LncRNA-SNHG5/ miR-1179/HMGB3 axis in NPC progression. Methods: RT-qPCR and Western blot analysis were employed to detect mRNA and protein expressions. CCK-8, Transwell and dual luciferase reporter assays were applied to investigate functions of LncRNA-SNHG5/miR-1179/ HMGB3 axis. Results: Upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…SNHG4 is not described for HNSCC, but in lung cancers it affects proliferation, migration and invasiveness, as well as EMT through miR-98-5p [ 52 ]. Similarly, SNHG5 in nasopharyngeal carcinoma regulates the expression of both the miR-1179/HMGB3 axis and cancer progression [ 53 ]. Finally, SNHG6 was indicated in the meta-analysis as an oncogene connected with cancer progression and could be used as a promising prognostic biomarker [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNHG4 is not described for HNSCC, but in lung cancers it affects proliferation, migration and invasiveness, as well as EMT through miR-98-5p [ 52 ]. Similarly, SNHG5 in nasopharyngeal carcinoma regulates the expression of both the miR-1179/HMGB3 axis and cancer progression [ 53 ]. Finally, SNHG6 was indicated in the meta-analysis as an oncogene connected with cancer progression and could be used as a promising prognostic biomarker [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gene detection performed by Liu et.al 18 in 64 NPC tissues and two NPC cell lines (NP69 and C666-1) indicated that the expression level of SNHG5 was remarkably increased in NPC tissues and cell lines (p < 0.05). Clinically, the relative higher expression of SNHG5 was tightly associated with advanced tumor stage and shorter overall survival.…”
Section: Nasopharyngeal Carcinoma (Npc)mentioning
confidence: 99%
“…9 In nasopharyngeal carcinoma, SNHG5 promoted tumor progression by regulating miR-1179/HMGB3 axis. 18 Moreover, SNHG5 targeted miR-154-5p to weaken the suppressive effect of miR-154-5p on PCNA, which was significantly involved in proliferation of breast cancer cells. 19 Furthermore, miR-26a-5p, which markedly suppressed GSK3β, was inversely correlated with SNHG5 in hepatocellular carcinoma.…”
Section: Biological Mechanisms Of Lncrna Snhg5 In Human Cancers Intermentioning
confidence: 99%
See 1 more Smart Citation
“…have been associated with many types of cancers including breast cancer, hepatocellular carcinoma, colorectal cancer, prostate cancer, acute promyelocytic leukemia, among others (reviewed in [52] and [53]), however, there is much quiescence regarding their role in NPC. Furthermore, only a few recent studies have demonstrated the upregulation of lncRNA small nucleolar RNA host genes (SNHGs) such as SNHG5 [54], SNHG7 [55,56], SNHG12 [57] and SNHG20 [58] in the blood and tissue samples of NPC patients. Thus, we focused on miRNA and long noncoding RNA for which there is more evidence to support the prognostic and diagnostic potentials in NPC, particularly using human subjects.…”
Section: Noncoding Rnas In Npcmentioning
confidence: 99%